Mental health in pregnancy and postpartum with the role of nurses: Integrative review (Research, Society and Development, 2024)
Lights and shadows that, over time, usually find their balance, allowing a good level of satisfaction and well-being, characterize motherhood. However, the path to achieving a full level of well-being can be long and full of obstacles. Postpartum depression is highly prevalent and affects mothers, babies and the family as a whole, and can result in numerous negative long-term effects, since most cases tend to last for long periods. The objective of this study is to discuss the factors that influence the mental health of pregnant women and mothers in the postpartum period, with an emphasis on the importance of diagnosing and treating postpartum depression and the role of nurses in this context. The study was conducted through an integrative review of the qualitative literature. The role of nurses collaborates with other specific professional figures who, due to their training and field of intervention, represent references for the obstetric patient. Helping women who suffer from depression is difficult because it is necessary to know how to welcome them and accompany them throughout the process. Care choices should not be random, and behavioural and professional attitudes should be targeted, since planning the most appropriate nursing care requires specific skills and technical knowledge. Recognizing symptoms and being able to talk about them freely with specialized professionals, such as nurses, is usually the first step to solving the problem. For these reasons, this is an extremely relevant topic for healthcare professionals.